Kemampuan Menulis Teks Berita Siswa Kelas VIII SMP Negeri 1 Tanah Putih - Mahrani, Annisa; Alber, Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study uses a descriptive method with a quantitative approach. The sample used in this study was 64 class VIII students at SMPN 1 Tanag Putih. Collecting data in this study using Observation Techniques  and Tests. Based on the results and discussion in the research on the ability to write news texts for class VIII students at SMP Negeri 1 Tanah Putih for the 2022/2023 Academic Year, it can be concluded that the average score of students’ ability in writing news texts based on the elements of news is 81.6 (categorized as good), and the everage score of students’ ability in writing news texts based on news presentation patterns is  67.68 (categorized as fair).